Multiomics analyses of gut microbiota and metabolites in people living with HIV before and during SARS-COV-2 infection - Xuebin Tian; Yiwen Xie; Yulong Zhao; Xiangyun Lu; Nanping Wu (Scientific Reports)
Abstract People living with human immunodeficiency virus (HIV) (PLWH) might have an increased risk of developing coronavirus disease 2019 (COVID-19); however, the impact of their gut microbiota and metabolites on the progress of COVID-19 is unknown. Herein, we analyzed the temporal changes in the gut microbiota composition and metabolites of PLWH at baseline and during severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. We analyzed the gut microbiota and metabolites by integrating 16 S rRNA gene sequencing and liquid chromatography-mass spectrometry untargeted metabolomics of 36 PLWH at baseline and during SARS-CoV-2 infection periods. Significant changes in the composition of the gut microbiota and an increased ratio of Firmicutes/Bacteroidetes during SARS-CoV-2 infection, relative to the baseline, were observed. At the genus level, the abundances of Lactobacillus and Lactiplantibacillus decreased significantly. Furthermore, seven differentially enriched human metabolic pathways (including protein digestion and absorption, central carbon metabolism in cancer, aminoacyl-tRNA biosynthesis, mineral absorption, ABC transporters, arginine and proline metabolism, and phenylalanine metabolism) were identified by comparing the fecal metabolites at baseline and during SARS-CoV-2 infection. Spearman correlation analysis revealed close relationships between the two differentially abundant microbiota members and the five differentially abundant fecal metabolites that might affect specific human metabolic pathways.This study is the first to characterize the gut microbiota and metabolites in PLWH at baseline and during SARS-CoV-2 infection. The key microbiota and metabolites in the infection process were identified, providing new ideas for treatment.